Determinação de impurezas elementares por espectrometria de absorção atômica em produtos farmacêuticos utilizados por pacientes com doença renal crônica - Maziero, Maiara (2023)
Patients with chronic kidney disease (CKD) have the functions of filtering fluids and excreting impurities from the body compromised. Often, these patients have comorbidities, requiring the use of various medications and, sometimes, food for special purposes. In this study, highresolution continuous source atomic absorption spectrometry equipped with a graphite furnace (HR-CS GFAAS) is proposed as a method for the determination of Al, Cd, Cu, Mo and Pb in pharmaceutical products commonly used by patients with CKD. , since its accumulation in the body can cause damage to the health of patients. Analytical conditions such as pyrolysis and atomization temperatures, use of chemical modifiers and sample preparation were optimized. Atomic absorption spectrometry was used for elemental determinations in drug samples after acid digestion carried out in a microwave oven. Furthermore, extraction induced by emulsion breakage was used as a technique for preparing food samples for special purposes, allowing the transfer of the elements of interest from the oily matrix to the aqueous extract. The validation parameters (linearity, analytical range, accuracy, precision, limit of quantification, limit of detection and specificity) are in line with what is stipulated by the American Pharmacopoeia. The concentrations of Cd, Cu and Mo were within the limits recommended by the Brazilian Pharmacopoeia in all drug samples (n = 63). However, seven drug samples showed higher amounts of Pb (concentrations ranging from 12% to 238% above the permitted limit) than the limits stipulated for this element. All samples analyzed showed relatively considerable concentrations of Al (concentrations ranging from 0.21 to 214.92 μg g-¹), in view of the health condition of patients with CKD. Additionally, a comparative study was carried out between reference, generic, similar and magisterial drugs containing captopril and losartan potassium. It was noticed that generic drugs, in general, had the highest concentrations of the elements selected for analysis. In addition, Cd concentrations in food samples for enteral nutrition intended for chronic kidney patients were below the limit allowed by Brazilian legislation (0.01 mg kg-¹). However, two samples presented Pb concentration (samples 4 and 5) above the allowed limit (0.01 mg kg-¹). Furthermore, all samples analyzed in this study showed relatively considerable amounts of Al (0.72–1.66 mg kg-¹). The methods proposed for quantitative determinations of the analytes of interest by HR-CS GFAAS after the different sample preparations used in this study proved to be simple, fast and efficient. Thus, medicines and food for special purposes can be sources of exposure to elemental impurities in chronic kidney patients. Thus, it can reduce the quality and survival of these individuals.